Thermal degradation studies of different polar polyethylene copolymers - (:unkn) unknown (My University, 2002)
The thermal degradation of different polar polyethylene copolymers, ethylene/methylacrylate (EMA), ethylene/ethylacrylate (EEA), ethylene/butylacrylate (EBA), ethylene/methylmethacrylate (EMMA), and ethylene/hydroxyethylmethacry-late (EHEMA), was studied by using thermogravimetric analysis (TGA), infrared analysis (FTIR), and size exclusion chromatography (SEC). Weight loss measurements of the different copolymers were performed at 333°C by using a nitrogen atmosphere in a TGA instrument. The samples thus aged were then characterized with the help of FTIR and SEC. Degradation reactions, such as ester pyrolysis, chain scission, and gelation, were investigated. EBA, EEA, and EHEMA undergo ester pyrolysis, which is affected by the structure of the ester moiety. EHEMA reacts additionally by transesterification and thus forms crosslinks. EMA and EMMA do not react by ester pyrolysis. It is concluded that the reaction products formed during ester pyrolysis support chain scission, and therefore, these reactions are observed more for EBA and EEA than for EMA and EMMA. Finally, the rate of chain scission is higher for EMMA than for EMA. This is explained as being due to an initiation of chain scission at the α-C-C bond, in which formed radicals are stabilized by the additional methyl group in EMMA. © 2002 Wiley Periodicals, Inc. J. Appl. Polym. Sci.
Keywords: Polyethylene; Thermal degradation